Local Signals and the Returns to Foreign Education - Massimiliano Tani (Institute for the Study of Labor (IZA), 2015)
This paper exploits a quasi-experiment to shed light on whether the wage penalty experienced by migrants reflects poor schooling quality in the country of education or employers' discrimination in the host country. The quasi-experiment is the possibility for migrants to undertake an official assessment of their foreign qualifications, and remove the uncertainty surrounding the educational curriculum completed abroad. Data about the assessment can be used together with indicators of where education was completed to test empirically which determinant most affects the returns to foreign education. Since the assessment is a choice it is instrumented with a measure of relative distance between awareness of degrees awarded in the country of education and the host country. The analysis is based on the Longitudinal Survey of Immigrants to Australia. The results suggest that undertaking the assessment raises the returns of foreign education, offsetting the penalty for being educated abroad. The assessment's effect weakens over time, as employers observe migrants' productivity. The effect of where schooling is completed also trends upwards over time. These findings are consistent with the hypothesis of statistical discrimination due to the imperfect information about migrants' educational credentials. Adding a local signal appears to be effective in easing immigrants' economic assimilation and improve the international transferability of their human capital.
Keywords: J24; J61; J70; 330; immigration; foreign education; statistical discrimination